Temporal Dynamics of Polyp Regression and Retreatment Burden in As-Needed VEGF Inhibitor Therapy: A 24-Month Study - Misa Kimura; Yoichi Sakurada; Yoshiko Fukuda; Yumi Kotoda; Kenji Kashiwagi (Pharmaceuticals, 2026)
Purpose: This study aimed to evaluate how the temporal dynamics of polyp regression influence 24-month outcomes in eyes with polypoidal choroidal vasculopathy (PCV) treated with as-needed vascular endothelial growth factor (VEGF) inhibitors. Methods: Sixty-three eyes of 63 patients were included. All patients initially received three monthly intravitreal injections of either aflibercept (2 mg) or brolucizumab, followed by as-needed treatment for 24 months. The selection of a VEGF inhibitor depends on time. Indocyanine green angiography (ICGA) was performed at baseline, 3 months, and 12 months in all patients. Results: Among the 63 eyes, complete regression was observed in 39 eyes (61.9%) at 3 months. Of these 39 eyes, 29 eyes (46.0%) maintained complete regression at 12 months. Among the 24 eyes that did not show complete regression at 3 months, 5 eyes (20.8%) achieved complete regression at 12 months. Visual acuity improved over 24 months regardless of the timing of regression. Early regression at 3 months was associated with fewer additional injections during the first year. In contrast, regression at 12 months—rather than at 3 months—was more strongly associated with fewer additional injections during the second year. Conclusions: The most recent status of the polypoidal lesion was associated with the number of additional injections during the corresponding 12-month period, suggesting that ICGA-based assessment may be important for predicting treatment responsiveness.